You Hurt Me, so I Hurt Myself and Others: How Does Childhood Emotional Maltreatment Affect Adolescent Violent Behavior and Suicidal Ideation? - Wang, Xiaoyue (Journal of interpersonal violence, 2022)
Violent behavior and suicidal ideation are two major public health problems, with the former representing outward attack and the latter characterizing inward attack. The effects of emotional maltreatment in childhood will continue into adolescence. This study explores the impact of childhood emotional maltreatment on adolescent violent behavior/suicidal ideation and its mechanism. Participants were 3,600 adolescents (average age is 16.21 ± 0.99) from the middle east of China. They completed questionnaires measuring emotional maltreatment in childhood, deviant peer affiliation, depression, violent behavior, and suicidal ideation in adolescence. After controlling for demographic variables, we found that deviant peer affiliation and depression mediated between childhood emotional maltreatment and adolescent violent behavior/suicidal ideation. Multi-group analysis results showed that males? deviant peer affiliation would contribute to their violent behaviors. Among female groups, deviant peer affiliation and depression were risk factors for violent behavior and suicidal ideation. a) cross-sectional design was used in this study; b) all the measures were self-reported. Preventing emotional maltreatment in childhood can help reduce violent behavior and suicidal ideation by reducing deviant peer affiliation and depression in adolescence. Males who experienced emotional maltreatment in childhood are more likely to show violent behaviors shaped by external factors such as deviant peer affiliation. In contrast, females? interpersonal orientation and internalizing factors both influence their external and internal aggressive behaviors.